How gate setup and turn radii influence energy dissipation in slalom ski racing - Supej, M.; Holmberg, H. C. (Journal of Applied Biomechanics, 2010)
This study examined whether gate setup and turn radii influence energy dissipation in slalom skiing. 3D kinematical measurements were performed over two runs on the same slope in a WC slalom competition with two different gate setups: 1) open gates (OG) and 2) open gates with a delayed gate (DG). Using the arithmetic mean of the skis` turn radii (RAMS) the slalom turns were divided into 1) initiation phase (RAMS > 15m) and steering phase (RAMS < 15m). The results show differences between OG and DG regarding: 1) the absolute center of gravity`s (CG) velocity, 2) absolute acceleration, 3) CG turn radii and RAMS, 4) ground reaction forces (F) and 5) energy dissipation during skiing (all p < .05). In both gate setups the highest F and the highest energy dissipation were present in the steering phase, whereas the correlation between RAMS and energy dissipation was low (OG: r = .364 and DG: r = .214, both p < .001). In summary, compared with plain open gates, an additional delayed gate prolonged the turn radii and decreased energy dissipation in the beginning of the initiation phase, despite the fact that the relative frequency of occurrence of the highest energy dissipation was higher in DG.